Experimental Testing Results on Critical Components for Molten Salt-Based CSP Systems - Valeria Russo; Giuseppe Petroni; Francesco Rovense; Mauro Giorgetti; Giuseppe Napoli; Gianremo Giorgi; Walter Gaggioli (Energies)
Concentrated Solar Power (CSP) plants integrated with Thermal Energy Storage (TES) represent a promising renewable energy source for generating heat and power. Binary molten salt mixtures, commonly referred to as Solar Salts, are utilized as effective heat transfer fluids and storage media due to their thermal stability and favorable thermophysical properties. However, these mixtures pose significant challenges due to their high solidification temperatures, around 240 °C, which can compromise the longevity and reliability of critical system components such as pressure sensors and bellows seal globe valves. Thus, it is essential to characterize their performance, assess their reliability under various conditions, and understand their failure mechanisms, particularly in relation to temperature fluctuations affecting the fluid’s viscosity. This article discusses experimental tests conducted on a pressure sensor and a bellows seal globe valve, both designed for direct contact with molten salts in CSP environments, at the ENEA Casaccia Research Center laboratory in Rome. The methodology for conducting these experimental tests is detailed, and guidelines are outlined to optimize plant operation. The findings provide essential insights for improving component design and maintenance to minimize unplanned plant downtime. They also offer methodologies for installing measurement instruments and electrical heating systems on the components.